1996
DOI: 10.1021/jp9530109
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Atom Attack on 1,2-Dichlorotetrafluoroethane:  Rates of Halogen Abstraction

Abstract: Hydrogen atom attack on 1,2-dichlorotetrafluoroethane (DCFE) at temperatures between 970 and 1140 K and pressures of about 200−500 kPa (2−5 bar) has been studied with a single-pulse shock tube reactor. The observed products show that chlorine is readily abstracted, while fluorine is removed in at most trace quantities only. This is despite the greater exothermicity of the fluorine abstraction channel. Relative to the standard reaction of displacement of methyl from 1,3,5-trimethylbenzene, for which k[H + (CH3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…In the present work, the minor channel-producing propene from HME (R1543) impacts results under some of our conditions. Tsang 52 reported approximate branching values, but we additionally use later unpublished work from our laboratory 52,70,87 that confirmed his results while better characterizing the temperature dependence (see Supporting Information). The rate constant for reaction of H with HME (R1544) was taken as that recommended for generic primary hydrogens in our recent review and evaluation.…”
Section: And Propene (R1543)supporting
confidence: 68%
“…In the present work, the minor channel-producing propene from HME (R1543) impacts results under some of our conditions. Tsang 52 reported approximate branching values, but we additionally use later unpublished work from our laboratory 52,70,87 that confirmed his results while better characterizing the temperature dependence (see Supporting Information). The rate constant for reaction of H with HME (R1544) was taken as that recommended for generic primary hydrogens in our recent review and evaluation.…”
Section: And Propene (R1543)supporting
confidence: 68%
“…Mesitylene reacts with hydrogen atoms to form either H 2 + 3,5-dimethylbenzyl radicals or m-xylene + methyl radicals. This latter reaction is the only source of m-xylene in this system, providing a means to determine H-atom concentrations, using the known 12 Methyl radicals can also abstract hydrogen from mesitylene to form CH 4 + 3,5-dimethylbenzyl radicals. The resonantly stabilized dimethylbenzyl radicals do not undergo significant further reaction during the heating pulse, effectively preventing H and CH 3 radicals from reacting with the reactant or reference species.…”
Section: Methodsmentioning
confidence: 99%
“…Mesitylene reacts with hydrogen atoms to form either H 2 + 3,5-dimethylbenzyl radicals or m -xylene + methyl radicals. This latter reaction is the only source of m -xylene in this system, providing a means to determine H-atom concentrations, using the known ratio of methyl displacement to H abstraction, k d / k a = exp(−1086/ T ). Methyl radicals can also abstract hydrogen from mesitylene to form CH 4 + 3,5-dimethylbenzyl radicals.…”
Section: Methodsmentioning
confidence: 99%
“…Rate constants for the reaction of OH radicals with hexamethylbenzene (HMB), k (OHϩHMB) , as well as for the H-atom reaction with both aromatics, k (HϩTMB) and k (HϩHMB) , are not available at least for the desired temperature region. As a result of a shock-tube study (T ϭ 970 -1140 K), a relative value for k (HϩTMB) is reported not applicable to room-temperature conditions [7]. Therefore, the subject of this work is to determine the rate constants k (OHϩHMB) , k (HϩTMB) , and k (HϩHMB) at room temperature.…”
Section: Introductionmentioning
confidence: 99%